SEANIMART: MENJAGA HAK CIPTA PENULIS NASKAH TEATER MELALUI SOSIALISASI HAK KEKAYAAN INTELEKTUAL - Umi, Aulia Yudatining; Nada, Rifa Qothrun; Chandra, Samuel; Laeliyah, Dini Soﬁa; Syaharani, Sabina; Damai, Imelia; Fidel, Mohammad; Saputri, Aifa; Noreen, Nisrina; Sabilah, Ardan; Putri, Bernadetta; Salma, Prameshwari; Nursaemah; Nova, Annisa; Alifah, Shabrina; Christy, Dinda; Apriliya, Dewi; Pitaloka, Erlinda Dyah Ayu; Kamelia, Eza Anisa; Ananda, Nadia; Ocean, M. Arel; Khoirunnisa, Aﬁfah; Putri, Sasqia (Zhata Institut, 2025)
SEANIMART is a strategic initiative aimed at protecting the copyrights of theater scriptwriters through the promotion of Intellectual Property Rights (IPR). Copyright, as part of IPR, is often misunderstood and undervalued, particularly in the performing arts industry. This program is designed to raise awareness among writers, theater practitioners, and the public about the importance of copyright protection in supporting a sustainable artistic ecosystem. The methods employed include workshops, seminars, and the dissemination of information through digital media. This program not only provides understanding of regulations and procedures for copyright protection but also fosters collaboration between scriptwriters, legal institutions, and art organizations. Through the implementation of SEANIMART, it is expected that theater scriptwriters will acquire sufficient knowledge and tools to safeguard their works, thereby creating an environment that values originality and creativity.